Glyphosate Biodegradation by Molybdenum-Reducing Pseudomonas sp. - Aliyu, Fatima Ibrahim; Ibrahim, Aminu; Babandi, Abba; Shehu, Dayabbu; Ya’u, Murtala; Babagana, Kamaluddeen; Ibrahim, Salihu; Abdullahi, Nasiru; Safiyanu, Aminu Jibril; Yakasai, Hafeez Muhammad (Journal of Environmental Microbiology and Toxicology, 2022)
Bioremediation of pollutants, such as herbicides, is an economic and environmentally friendly process. Glyphosate is an active ingredient in most herbicides utilized for weed control and desiccation on cereal and other grain crops globally. Glyphosate pollution poses a threat to the environment and the habitats in it. In this study, an isolated molybdenum-reducing bacterium was characterized for its potential to degrade glyphosate and utilized as the sole source of carbon and electron donor. The effects of incubation time, glyphosate concentration (carbon source), inoculum size, pH, temperature, aeration and heavy metals on the growth of this bacterium were spectrophotometrically assayed as OD600 nm. The bacterium degrades glyphosate faster under shaking conditions, optimally at pH 7.0, concentration 1.0 g/L, temperature 40 ºC, and inoculum size 400 µL. Growth of this bacterium was significantly inhibited by heavy metals in the order of Cu>Zn>Pb>Hg>Ag>Fe compared to the control. Glyphosate can serve as an electron donor source in hexavalent molybdenum reduction, but poorly supports molybdenum blue (Mo-blue) production compared to glucose. The dual role of this isolate as a metal reducer and glyphosate degrader makes it unique already and an important instrument for the bioremediation of mixed pollutants.